Economic aspects of intraoperative coagulation management targeting higher fibrinogen concentrations during major craniosynostosis surgery. Issue 1 (12th October 2015) - Haas, Thorsten; Spielmann, Nelly; Restin, Tanja; Schmidt, Alexander R.; Schmugge, Markus; Cushing, Melissa M.
Summary: Background: Results of a previously published study demonstrated a significant decrease in transfusion requirements and calculated blood loss for pediatric major craniosynostosis surgery, if a ROTEM ® FIBTEM trigger of <13 mm (early substitution group) was applied as compared to a trigger of <8 mm (conventional group). The aim of this study was a posthoc analysis of the costs for this coagulation management. Methods: The total volume as well as the number of units or bags for all transfused blood products and coagulation factors were recorded for each case. The number of laboratory and point‐of‐care coagulation tests was also analyzed. Total blood product costs were calculated according to the local prices per unit. Results: The total cost for all transfused/administered blood products/coagulation factors per patient was a median of 1023EUR (IQR 850EUR–1058EUR) in the early substitution group as compared to a median of 910EUR (IQR 719EUR–1351EUR) in the conventional group ( P = 0.81). No difference in the number of coagulation tests performed was observed. Conclusion: In this study, the use of a higher fibrinogen trigger was not linked to a significant increase in total costs for transfused blood products and coagulation factors, and may offer an economically equivalent approach to coagulation management. Abstract :